Trail camera video systems: investigating their utility in interpreting patterns of marine, recreational, trailer-boat fishers' access to an offshore Marine Park in differing weather conditions. (25th November 2020) - Lynch, T P; Foster, S; Devine, C; Hegarty, A; McEnnulty, F; Burton, M; Lyle, J M
Abstract: When monitoring marine recreational fishers at sub-bio-regional scales—for example those who are accessing a Marine Park—on-site sampling is often required. This poses various logistical challenges, such as the efficient timing of intercept interviews. Here, we examine these challenges, combining trail cameras, closed-circuit television (CCTV), weather stations, and interviews at boat ramps that bracket an offshore Marine Park. Trail camera results were similar to those from a CCTV system co-located at one of the boat ramps. Fishers' boat launches peaked early, but return times varied considerably by ramp and weather. Both the numbers of launches and trip durations were strongly responsive to good weather, particularly at ramps used for offshore fishing. Weather was a more important factor to predict the likelihood of intercept interview opportunities than holiday period, which may reflect changing dynamics in work culture and improvements in weather prediction. Interviewed fishers reported preferences to individual ramps over the fishing season and nearly all trips to the Marine Park were reported by fishers accessing just one ramp. The strong relationships between fishing, weather, and ramp, observed by the trail camera and correlated with the weather station data, may allow for the efficient targeting of intercept interviews and potentially the modelling of fishing effort.